Answer:
all real numbers
Step-by-step explanation:
Simplifying
4(x + 1) = 4x + 4
Reorder the terms:
4(1 + x) = 4x + 4
(1 * 4 + x * 4) = 4x + 4
(4 + 4x) = 4x + 4
Reorder the terms:
4 + 4x = 4 + 4x
Add '-4' to each side of the equation.
4 + -4 + 4x = 4 + -4 + 4x
Combine like terms: 4 + -4 = 0
0 + 4x = 4 + -4 + 4x
4x = 4 + -4 + 4x
Combine like terms: 4 + -4 = 0
4x = 0 + 4x
4x = 4x
Add '-4x' to each side of the equation.
4x + -4x = 4x + -4x
Combine like terms: 4x + -4x = 0
0 = 4x + -4x
Combine like terms: 4x + -4x = 0
0 = 0
Solving
0 = 0
Couldn't find a variable to solve for.
This equation is an identity, all real numbers are solutions.